Diaries and correspondence. Containing an account of his missions to the courts of Madrid, Frederick the Great, Catherine the second, and The Hague. And his special missions to Berlin, Brunswick, and the French Republic. Ed. by his grandson [James Howard Harris, Earl of Malmesbury] (Bentley, 1844)
With index and prts.